2013
DOI: 10.1186/1756-9966-32-63
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism modifications and apoptosis induction after Cellfood™ administration to leukemia cell lines

Abstract: BackgroundCellfood™ (CF) is a nutritional supplement containing deuterium sulphate, minerals, amino acids, and enzymes, with well documented antioxidant properties. Its organic and inorganic components are extracted from the red algae Lithothamnion calcareum, whose mineral extract has shown growth-inhibitory effect both on in vitro and in vivo models. The purpose of this study was to evaluate the antiproliferative effects of CF on leukemic cells. In fact, according to its capacity to modulate O2 availability a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
0
17
0
Order By: Relevance
“…Caspase-3 is considered to be the most important effector of apoptosis and a marker for both intrinsic and extrinsic pathways [37]. An important aspect to consider is the chemical structure of the different MAGs, which affects the potency to induce apoptosis; in this regard, Philippoussis et al [3] concluded that SFA-based MAG had no effect on such phenomenon, while PUFA-MAGs were highly potent to induce apoptosis in T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Caspase-3 is considered to be the most important effector of apoptosis and a marker for both intrinsic and extrinsic pathways [37]. An important aspect to consider is the chemical structure of the different MAGs, which affects the potency to induce apoptosis; in this regard, Philippoussis et al [3] concluded that SFA-based MAG had no effect on such phenomenon, while PUFA-MAGs were highly potent to induce apoptosis in T-cells.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic DNA fragmentation was evaluated after 6, 24 and 48 hours upon PLEO administration (0.04% v/v, 320 μg/ml) by agarose gel electrophoresis, as previously described [ 20 ]. DNA samples were carefully resuspended in TE buffer; nucleic acid concentration and purity were measured using a NanoDrop® ND-1000 spectrophotometer (Thermo-Scientific, Wilminton, DE, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Overall, these results provide evidence that curcumin warrants further investigation as a therapeutic agent in MM, although future studies must include improved curcumin analogs or enhanced modes of delivery to overcome curcumin's most challenging feature, which is limited bioavailability. Other than protecting biomolecules and cells from oxidative damage [ 193 ], evidence has been recently supplied for an anti-cancer activity of Cellfood™ (CF) [ 194 , 195 ]. Apoptotic death was observed in CF-treated MSTO-211H.…”
Section: Introductionmentioning
confidence: 99%